Jenis-Jenis Layanan Bimbingan dan Konseling dalam Mendukung Perkembangan Peserta Didik Sekolah Dasar - Riska Auliya; Titi Sunarti; Rizka Mutiara; Azzahra Dwi Damayani; Risti Fauziah (Jurnal Pendidikan Dirgantara, 2026)
Guidance and counseling constitute a crucial element in the educational structure of elementary schools, functioning to support students’ holistic development, including academic, social, emotional, and personal aspects. As students at this level are in the early stages of development, they require systematic guidance to actively adapt to the school educational context while optimizing the development of their potential to an optimal level. This study aims to examine the variety of guidance and counseling services in elementary schools and their role in addressing students’ problems through a literature review of relevant scientific sources, including national and international journals as well as reference books published after 2020. The results indicate that the implementation of guidance and counseling at the elementary school level encompasses various forms of services, such as orientation to the school environment, information services, placement and referral guidance, group guidance activities, individual and group counseling services, consultation, and mediation efforts. These services contribute to helping students overcome learning difficulties, behavioral problems, social adjustment issues, and personality development. However, their implementation still faces several challenges, including a shortage of professional personnel and teachers’ limited understanding of guidance and counseling. Therefore, it is essential to strengthen guidance and counseling programs in elementary schools in a well-planned and sustainable manner.